Plantas alimentícias não convencionais (PANC) - a divulgação científica das espécies na cidade de Manaus - Borges, Carla Karoline Gomes Dutra (2017)
The Non-Conventional Food Plants - PANC, has been gaining space in the media, academic works, supermarkets, fairs and also in the homes of consumers of these vegetables. This research aimed to verify whether or not the scientific dissemination of the species of unconventional food plants found in the city of Manaus, highlighting its potential as a food resource for the Manauara population has occurred. The research sites were five fairs of the city of Manaus, being: Municipal Producer Fair; Manaus Modern Fair; Crowned Fair; Fair of the Dawn and Fair of the SEPROR. As data collection technique we used the Case Study, which allows us to use a variety of data collection instruments. Thus, for this work, we use the interview, the direct observation, the field diaries and the physical artifacts to have a greater understanding about our investigated object. As a way of analyzing the data, we used the Content Analysis, associated to TTR (type token ratio) that provided the necessary indicators for the analysis. Therefore, we identified three indicators (categories) present in this study that were: i) The use of PANC; ii) The dissemination of the PANC; iii) The importance of NonConventional Food Plants (NRPs). It is worth mentioning that the analytical categories are the same indicators also found from the TTR (token ratio) technique, thus validating the entire categorization process. For each category / indicator found, we write explanatory text. In the category of PANC use, we observe that they are widely used by people, but with the nomenclature of medicinal plants, and these people use them without knowing their food potential, thus causing the species to be considered only as medicinal, not knowing the food associations for these species. In the category of dissemination of PANC, we frequently observe the lack of knowledge of the population about food properties and even the identification of species suitable for food. However, the food issue of the species was always conjugated to medicinal property, which is something very present in our records. Many interviewees have pointed to television as one of the means by which food plants could be widely disseminated, as well as citing other media such as books and exhibitions. The third category, which is the importance of PANC, is intimately linked to the family issue where most people associate importance with some healing effect or preparation to solve something, where we again perceive the association of PANC with medicinal plants. In this category the words mother, grandmother and family are very recurrent, thus evidencing the importance of the family in the transmission of this knowledge. Therefore, we understand that the lack of information on unconventional food plants contributes to its lack of knowledge. We believe that the role of dissemination of these species associated with their importance is a key landmark for the dissemination of this knowledge that can not be prevented from future generations.